China's agrarian transition : peasants, property, and politics - Trappel, René (Challenges facing Chinese political development., 2016)
This empirical case study of the current transformation of Chinese agriculture explores the role of property institutions, peasant differentiation, and rural politics in the formation of a market for agricultural land-a crucial step in the transition from smallholder farming to large commercial enterprises.